The Idea of the Beautiful in the Sources of Islam - Bejtić, Alija (Prilozi za orijentalnu filologiju, 2017)
The theoretical discussion on whetlıer or not there exists in Islam as a the- ological and philosophical doctrine the concept of the beautiful in the esthe- tic sense or whether or not Islam has an attituđe toward ari and what that at- titude is, has long been carried on. The author has undertaken to consider that question directly in the Qur’an and Muhammad’s tradition (hadith); he has deliberately taken these sources only in order to elucidate the idea of the beautiful in Islam in the very beginning, apart from the attitudes expressed in the latter Islamic literature. The author has reached these conclusions: In pre-Renaissance civilizations, including Islam and the Islamic world as well, the idea expressed in modern times by the term art was expressed by the terms beauty and beautiful. The connection between the terms beauty and art having been established in this way makes it possible for us to see an en- tire little world in the qouted sources of Islam, where we encounter not only the concept of the beautiful and beauty, but also a representation of the object of beauty and even judgments of these objects as true bearers of the idea of the beautiful. Both the Qur’an and the hadith communicate in the language which is understood by the common man. Having this in view, and as both the Qur’an and the hadith contain a large number of wxamples of esthetic evaluation (understanding, valorization), it means accordingly that the pre-Islamic Arab society in Hijaz, in which the Qur’an and the hadith apeared, had a certain cultural and philosophical foundation which made it possible for the idea of the beautiful to be received and comprehended. Several pieces of evidence concerning this have been quoted. A terminology of esthetic notions taken directly from the texts of the Qur’an and the hadith has also been provided. The author quotes the hadith: “Allah is beautiful and loves beauty” (Allâhu ğamTİ wa yuhibbu-1-ğamâl) and other examples and concludes that according to basic principles of Islam beauty is a divine capacity. He also States that according to these same sour- ces the idea of the beautiful exists both in things which are the product of human hands and in thing produced by nature itself (pineapple fruit, shell of a snail, honeycomb, etc.). The last chapter deals with the worlds of the beautiful according to the principa! quoted sourees of Islam: the author concludes, quoting texts from the Qur’an and the hadith, that Islam sees beauty, and also art, in the unity of the cosmos, in nature, in the proportions of the human organism, and in that which is the product of human hands. He fmds evidence of the positive atti- tude of Islam toward the beauty of nautre in the descriptions of paradise, which greatly emphasize the beauty of the vegetation, water and landscape. Anaiyzing the attitude of Islam to the beauty of human organism, the author comes to the important discovery that the Arabs knew of the notion of the golden section or cut (Lat. sectio aurea) as early as the first half of the seventh century (the time of the appearance of the Qur’an). In the end the author writes about the cult of the green color among Mus- lims. He claims that the cult was introduced because of the overemphasized green color of the world of paradise in many quotations in the Qur’an and the hadith. He thinks that the green color was introduced in the Qur’an and the hadith as a visiof the landscape and the color that dominates the vegetable nature of the rare Arab desert oases. Conclusion: Islam does have an attitude toward art; that attitude is, more- over, strongly emphasized and, what is more important, positive. Accordingly, there exists also an esthetics of Islam, only it is not systematized but expres- sed in the form of individual, unconnected views and thus in a form we might call basic foundations of esthetic.